Optimization Analysis of Gear Micro Parameters of Hybrid Transmission Cases - Li Qinyi; Chen Yiqing; Zhang Xi; Wang Hui; Luo Qin (Jixie chuandong)
The optimization analysis of gears in a hybrid transmission is carried out using the micro-modification module in the simulation platform of system analysis software MASTA，aiming at the vibration and noise problems of gear meshing in hybrid transmission. By comparing the transmission error between gears before and after modification and the contact stress nephogram of the tooth surface, the effectiveness of micro-modification based on system analysis software MASTA is verified, which provides a reliable theoretical basis for actual modification. The analysis results show that the transmission error of the gear is obviously reduced after micro-modification, and the contact stress nephogram of the tooth surface has been improved to a great extent, which plays an active role in reducing the vibration and noise of the gear. Finally, the data collection and comparative analysis of vibration and noise of gears in transmission are carried out. The results show that the corresponding box vibration acceleration and gear noise will be significantly improved after the micro-modification of the gear pair.